Resdescription of two synhymeniid ciliates, Chilodontopsis simplex Ozaki & Yagiu, 1941 and Zosterodasys transverses (Kahl, 1928) Foissner et al., 1994 (Alveolata, Ciliophora, Phyllopharyngea) - Wang, Lijuan; Zhao, Yuanjun; Gong, Jun (Zootaxa, 2012)
The morphology and infraciliature of two synhymeniid ciliates, Chilodontopsis simplex Ozaki & Yagiu, 1941 and Zoster-odasys transverses (Kahl, 1928) Foissner et al., 1994, collected from coasts of Qingdao, China, and Incheon, South Korea,respectively, have been investigated using live observation and protargol impregnation method. Chilodontopsis. simplexis characterized by: cell size 90–160 × 45–95 µm in vivo, oval to long elliptical in outline; 59–78 somatic kineties, 11–13nematodesmal rods; synhymenium constricted to ventral side, composed of 45–90 dikinetids, running across cell width;single contractile vacuole located in posterior cell end. The marine population of Zosterodasys transverses is briefly de-scribed, linked to the previously reported 18S ribosomal RNA gene (Genbank accession number EU286812), and compared to the freshwater population.